Performance analysis of Korea's new growth engine promotion program using total factor productivity analysis. (2018) - Park, Chansoo; Lee, Dong Woo
Korea's New Growth Engine Promotion Program has aimed to foster technologically competitive firms through public R&D support since 2009. This study analyses the outcomes of the program by focusing on firms' technological competitiveness. It uses total factor productivity (TFP) analysis and financial data on around 2500 Korean firms (2006~2014). We first find that solar energy, fuel cell, and wind power brands show accelerated policy effects with linearly increasing TFP. Second, the convergence network, wireless communication, and realistic DTV brands show reduced policy effects over time because of the redundancy between public R&D support and their own R&D strategies. Further, robot, game, and nano-materials brands in the early stages of the markets show no typical pattern due to their lack of absorptive capacity for the public R&D support. Thus, in order to generate positive policy outcomes, R&D support policies must be tailored to each new growth engine brand based on their absorptive capacities.